2014
DOI: 10.1115/1.4026040
|View full text |Cite
|
Sign up to set email alerts
|

Computational Studies on Metal Foam and Heat Pipe Enhanced Latent Thermal Energy Storage

Abstract: Thermal energy storage is a distinguishing component of a concentrating solar power (CSP) system, which enables uninterrupted operation of plant during periods of cloudy or intermittent solar availability. Latent thermal energy storage (LTES) which utilizes phase change material (PCM) as a heat storage medium is attractive due to its high energy storage density and low capital cost. However, the low thermal conductivity of the PCM restricts its solidification rate, leading to inefficient heat transfer between … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
18
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 57 publications
(18 citation statements)
references
References 26 publications
0
18
0
Order By: Relevance
“…It is concluded that with fin-structure, energy efficiency is improved significantly. Nithyanandam and Pitchumani [71] conducted numerical analysis on LHSTES system with metal foam and embedded heat pipe. It is reported that the augmentation in heat transfer rate during charging decreased with pore-density of metal foam, due to the restriction in the formation of buoyancy-induced convection.…”
Section: Combined Heat Transfer Enhancement Techniquesmentioning
confidence: 99%
“…It is concluded that with fin-structure, energy efficiency is improved significantly. Nithyanandam and Pitchumani [71] conducted numerical analysis on LHSTES system with metal foam and embedded heat pipe. It is reported that the augmentation in heat transfer rate during charging decreased with pore-density of metal foam, due to the restriction in the formation of buoyancy-induced convection.…”
Section: Combined Heat Transfer Enhancement Techniquesmentioning
confidence: 99%
“…However, a major technology barrier that is limiting the use of latent thermal energy of PCM is the higher thermal resistance provided by its intrinsically low thermal conductivity, thus requiring large heat transfer surface area of interaction. Several techniques to improve the thermal performance of latent thermal energy storage systems are reported in the literature; notable among them are embedding heat pipes or thermosyphons between the HTF and PCM [2][3][4][5], dispersing high conductivity particles in the PCM [6] and storing PCM within the framework of porous metal foams [7,8]. A review of various techniques employed to enhance the performance of high temperature latent thermal energy storage system is discussed in Ref.…”
Section: Introductionmentioning
confidence: 99%
“…The second term models the presence of the solid part in the mixed region, where the small number (0.001) avoids the division by zero [15] when β is null. Amush is the mushy zone constant which represents the damping of the velocity to zero during the solidification [18].…”
Section: Physical Modelmentioning
confidence: 99%
“…where t is the time, μPCM is the viscosity of the PCM or Nano-PCM; p is the relative pressure and S is a source term vector that includes all of following terms [15]:…”
Section: Physical Modelmentioning
confidence: 99%
See 1 more Smart Citation